Plasma heating assisted interfacial polymerization for making reverse osmosis membranes
Patent Information
- Application Number
- CN202410920943.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-24
- Filing Date
- 2024-07-10
- Publication Date
- 2025-01-24
Smart Images

Figure CN119345915A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Patent Application No. 63 / 528,550, filed on July 24, 2023, which is hereby incorporated by reference in its entirety. Technical Field
[0003] The present invention relates to a plasma heating assisted interfacial polymerization method for preparing high performance reverse osmosis membranes, and more particularly, to using the method with the prepared membranes to achieve generally high removal rates for various water pollutants. Background Art
[0004] Conventional reverse osmosis (RO) membranes are limited by the permeability-selectivity tradeoff and are often unable to adequately remove toxic and hazardous contaminants such as boron in seawater, arsenic (III) in groundwater, and endocrine disruptors in wastewater. With four billion people lacking access to reliable clean water, water scarcity is becoming a pressing challenge worldwide [1]-[2]. Reverse osmosis (RO) plays a significant role in addressing this challenge by increasing the global freshwater supply by approximately 21 billion gallons per day through seawater desalination [3]-[4]. In addition, its ability to produce clean water from wastewater, groundwater, and other non-traditional water sources offers great potential for further alleviating water scarcity [5]-[8]. However, existing polyamide RO membranes are strongly limited by the permeability-selectivity tradeoff: increasing water permeability generally results in decreased water-salt selectivity, and vice versa [9]-
[11] . At the same time, they are unable to adequately remove toxic and hazardous pollutants, such as boron in seawater
[10] ,
[12] -
[14] , arsenic (As(III)) in groundwater
[15] -
[17] , and endocrine disrupting compounds (EDCs) in wastewater
[18] -
[20] , which pose a serious threat to the safety of product water. These limitations require the development of high-performance RO membranes for various water treatment scenarios to efficiently produce clean water.
[0005] The separation performance of polyamide RO membranes depends largely on the characteristics of their polyamide layer
[21] -
[22] . This layer is usually prepared by interfacial polymerization (IP) reaction on a porous substrate. Specifically, amine monomers diffuse from aqueous solution into organic solution to react with acyl chloride at the water / organic interface. In principle, the heat generated by the IP reaction can promote interfacial degassing / evaporation, resulting in the formation of a polyamide structure containing nanocavities, as shown in Figure 1A
[23] -
[27] . This "nanofoaming" structure is highly correlated with the membrane water permeability
[23] ,
[27] -
[30] . At the same time, the generated reaction heat affects the diffusivity and reactivity of the monomers, which significantly affects the cross-linking degree of the polyamide and thus the membrane selectivity
[11] ,
[31] ,
[32] . It is speculated that effectively controlled local heating at the interface can enhance the IP reaction to break the permeability-selectivity trade-off and achieve widespread removal of pollutants. To achieve this goal, plasma-induced localized photothermal effects show great promise.
[0006] Specifically, due to the strong plasmon resonance of metal nanoparticles (e.g., silver) under visible or infrared light irradiation, solar energy can be efficiently converted into heat on the surface of these nanoparticles
[33] -
[36] . This plasmon photothermal phenomenon has been widely used to generate local heating in solar steam generation
[37] , photocatalysis
[38] , cancer therapy
[39] , molecular delivery
[40] , and other photothermal-related applications
[33] -
[36] . Summary of the invention
[0007] The present invention is an improvement on the existing interfacial polymerization method for preparing reverse osmosis (RO) membranes. Compared with the existing method, the present invention integrates plasma-induced photothermal conversion into the IP process to achieve in-situ interfacial plasma heating to strengthen the interfacial polymerization process, thereby customizing the polyamide layer to significantly improve the formation of the RO membrane, so that the prepared RO membrane can achieve excellent separation performance.
[0008] In the implementation of the present invention involving interfacial plasma heating enhanced IP reaction (IPH-IP) to prepare high permeability and selectivity polyamide RO membranes, silver nanoparticles (AgNPs) are introduced into the IP reaction interface to act as nanothermal generators under light irradiation, e.g. Figure 1B The resulting nanothermal coupling rapidly increases the interfacial temperature, thereby promoting the formation of extensive “nano-foamed” polyamide with significant nanocavities and high cross-linking degree. These features enable the resulting RO membrane to achieve a water permeability of 3.4 L m -2 h -1 bar -1) and NaCl rejection (99.7%), which largely breaks the permeability-selectivity trade-off. This excellent separation performance further enables the membrane to widely and efficiently remove common toxic pollutants in different water sources, thus showing great potential for various water treatment application scenarios. In addition, the RO membrane demonstrated efficient desalination of real seawater, producing high-quality clean water far exceeding the benchmark commercial membrane.
[0009] To reiterate, according to the present invention, interfacial plasma heating induced by silver nanoparticles can enhance interfacial polymerization for mass production of "nano-foamed" polyamides with significant nanocavities and high crosslinking. These features enable the resulting reverse osmosis membranes to simultaneously achieve high water permeability and interception of salts and various toxic pollutants in water. The present invention is the first example of the integration of interfacial plasma heating induced by silver nanoparticles to enhance interfacial polymerization to prepare high permeability and selective polyamide reverse osmosis membranes for multifunctional water purification.
[0010] Prior literature uses silver nanoparticles as an intermediate layer confined between a substrate and a polyamide layer
[42] . The water layer around each hydrophilic nanoparticle can induce the hydrolysis of trimesoyl chloride monomers, thereby terminating the interfacial polymerization. This effect can produce nanochannels with a size of approximately 2.5 nm around the AgNPs, which helps to improve the water permeability of the membrane. However, according to the present invention, during interfacial polymerization, the AgNPs utilize and induce an interfacial plasma heating effect under light irradiation, which can adjust the membrane separation performance. This interfacial plasma heating effect has not been previously reported for the preparation of polyamide reverse osmosis membranes.
[0011] Other existing literature proposes a simple process of loading AgNPs on the surface of a thin film composite reverse osmosis membrane as a coating
[41] . This AgNP coating is used to inhibit the formation of biofilm on the membrane surface, helping to enhance the biofouling characteristics. The formation of AgNPs on the membrane surface leads to a decrease in the water permeability of the membrane; however, the present invention significantly increases the water permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The above-mentioned advantages of the present invention in addition to other purposes will become more apparent when taken in conjunction with the following detailed description and the accompanying drawings, in which like reference numerals represent like elements, and wherein:
[0013] FIG. 1A is a schematic depiction of a conventional interfacial polymerization (IP) process, wherein the heat generated by the IP reaction can promote interfacial degassing / evaporation, thereby forming a polyamide structure containing nanocavities. Figure 1B is a schematic depiction of the IPH-IP process of the present invention, wherein silver nanoparticles (AgNPs) are introduced into the IP reaction interface to act as nanothermal generators under light irradiation;
[0014] Figure 2 The XRD patterns of PSf substrate and AgNP-modified PSf substrate are depicted;
[0015] Figures 3A-3D Modified PSf substrates with different AgNP loadings are depicted ( Figure 3A Labeled as "substrate", Figure 3B Marked as "Sub-Ag50", Figure 3C Marked as "Sub-Ag200", Figure 3D Marked as "Sub-Ag400");
[0016] Figure 4 is with Figures 3A-3D UV-VIS-NIR absorption spectra corresponding to each of the four substrates;
[0017] Figures 5A-5D is with Figures 3A-3D Infrared thermal images under sunlight corresponding to the four substrates;
[0018] Figures 6A-6D Depicts TEM images of cross-sections of polyamide membranes obtained using IPH-IP of 0 mM, 50 mM, 200 mM, and 400 mM AgNO3 solutions, Figure 6E-6H Depicted are SEM images of the surface of polyamide membranes obtained by IPH-IP using 0 mM, 50 mM, 200 mM, and 400 mM AgNO3 solutions;
[0019] Fig. 7A is a bar graph of the percentage of voids in the polyamide layer measured using TEM. Figure 7B is a bar graph of the degree of cross-linking of the polyamide layer, Figure 7C is a graph of the zeta potential of the membrane, Fig.7D is 1kW / m 2 Bar graph of the separation performance of membranes with different AgNP loadings (i.e., using PSf substrate, Sub-Ag50, Sub-Ag200, and Sub-Ag400) at light intensities of 1.3 Å. Fig. 7E At different light intensities (kW / m 2 ) with the same AgNP loading (i.e., using Sub-Ag200), Figure 7F is a graph showing the separation performance of the results of the present invention (red stars) in terms of water permeability and water / NaCl selectivity compared with existing literature data (black circles);
[0020] Figures 8A-8D Depicted are TEM images of membrane cross sections of polyamide membranes with and without AgNPs and with and without illumination. Figures 8E-8Hdepicts SEM images of the surface of polyamide membrane with and without AgNPs and with and without light irradiation;
[0021] Fig. 9 is a bar graph of the separation performance of polyamide membranes with and without AgNPs and with and without light irradiation;
[0022] Figures 10A-10D TEM images of a cross section of a polyamide film at different wavelengths of light are depicted. Figures 10E-10H Depicted are SEM images of the surface of a polyamide membrane at different wavelengths of light;
[0023] Fig.11 is a bar graph depicting the separation performance of polyamide membranes at different wavelengths of light;
[0024] Figures 12A-12D Plotted at different light intensities (kW / m 2 ) is a TEM image of a cross section of a polyamide membrane. Figures 12E-12H Plotted at different light intensities (kW / m 2 ) of the surface of the polyamide membrane under different SEM photographs;
[0025] Fig.13 is a bar graph depicting the separation performance of polyamide membranes prepared from different plasmonic nanomaterials (i.e., Cu and Ag);
[0026] Fig.14 Corresponding to Na + , K + , Cl - and SO4 2- Bar graph of the actual seawater concentrations and their rejection by the membrane;
[0027] Figures 15A-15C 3D fluorescence spectra corresponding to dissolved organic matter in real seawater and membrane permeate;
[0028] Fig.16A is a bar graph of the rejection of B (5 ppm at a typical seawater pH of ∼8.5) and As(III) (5 ppm at a typical groundwater pH of ∼8.5), Fig. 16B is a graph of the rejection of N (15 ppm at a typical wastewater pH of ˜7.5) and P (1 ppm at a typical wastewater pH of ˜7.5), Fig. 16C is a graph of the rejection of various EDCs (200 ppb at a typical wastewater pH of ~7.5);
[0029] Fig.17Figure 2 is a graph showing the retention rate of TFC-Ag200L for 17 common harmful pollutants in different water sources (e.g., boron in seawater, As(III) in groundwater, N, P, EDC, antibiotics, and PFAS in wastewater) and the retention rate of 6 typical ions. The error bars represent the standard deviation using three different samples. DETAILED DESCRIPTION
[0030] When implementing the method of the present invention, various chemicals are used. In particular, a polyamide layer is prepared on a polysulfone (PSf) substrate (MWCO 67kDa, Vontron Technology) by interfacial polymerization (IP) reaction using m-phenylenediamine (MPD), trimesoyl chloride (TMC) and n-hexane obtained from Sigma-Aldrich. Silver nitrate (AgNO3, Sigma-Aldrich) and sodium borohydride (NaBH4, Dieckmann) are used to generate AgNPs in situ on the substrate. Sodium chloride (NaCl, Dieckmann) is used for separation performance testing. Boric acid (B(OH)3, Dieckmann) and arsenic (III) oxide (As2O3, Dieckmann) are used as model pollutants in seawater and groundwater, respectively. Sodium dihydrogen phosphate (NaH2PO4, Dieckmann) and ammonium chloride (NH4Cl, Dieckmann) are used as inorganic model pollutants in wastewater. Endocrine disrupting chemicals (EDCs, including methylparaben (MP), ethylparaben (EP), propylparaben (PP), and benzylparaben (BP)) obtained from Sigma-Aldrich were used as organic model pollutants in wastewater.
[0031] The conventional polyamide RO membrane was prepared as follows: First, the PSf substrate was immersed in a 2 w / w% MPD solution for 2 minutes. After removing the excess MPD solution by a rubber roller, the substrate was immersed in a 0.1 w / w% TMC / hexane solution for 1 minute to form a polyamide layer. The prepared polyamide RO membrane was named TFC.
[0032] The IPH-IP reinforced polyamide RO membrane of the present invention is prepared as follows. First, AgNPs are generated in situ on a PSf substrate according to published literature
[41] -
[42] . Briefly, the PSf substrate is soaked with AgNO3 solution (50 mM, 200 mM or 400 mM) under the condition of shaking at 50 rpm for 10 minutes. The extra AgNO3 solution is removed by a rubber roller. Then, NaBH4 solution (200 mM) is poured on the PSf substrate to infiltrate silver ions (AgNPs) under the condition of shaking at 50 rpm for 10 minutes. +) was reduced to AgNP. The substrate was then rinsed with deionized (DI) water for 5 minutes. According to the amount of Ag contained, the AgNP-modified substrates were named sub-Ag50, sub-Ag200, and sub-Ag400. Finally, the AgNP-modified substrates were used to filter the air at 1 kW / m 2 The polyamide layer was prepared by IP reaction under simulated sunlight irradiation (xenon lamp, CEL-S500, obtained from Beijing Jin Yuan Science and Technology Co., China). The prepared polyamide RO membrane was named TFC-Ag AgNO3 concentration L, for example, TFC-Ag200L means that it was prepared using 200mM AgNO3 under sunlight irradiation. In order to further study the effect of light irradiation, different light wavelengths (two bandpass filters were used for light wavelengths of ~400nm and ~600nm respectively) and intensities (0.5kW / m 2 , 2kW / m 2 and 4kW / m 2 ) were used to prepare polyamide RO membranes. These membranes were named TFC-Ag200L-400nm, TFC-Ag200L-600nm, TFC-Ag200L-0.5, TFC-Ag200L-2 and TFC-Ag200L-4.
[0033] The film is then characterized. Under an accelerating voltage of 5kV, PSf substrates and polyamide film surfaces with and without AgNPs are characterized by field emission scanning electron microscopy (FE-SEM, S-4800, Hitachi). All SEM samples are dried in an oven at 40°C and then coated with gold sputtering for 40 seconds before characterization. The formation of AgNPs on substrates is characterized by X-ray diffraction (XRD) patterns recorded by RigakuUltima IV. The light absorption spectrum (300nm to 2500nm) of substrates is measured using UV-VIS-NIR spectroscopy (UV-3600i Plus, Shimadzu) equipped with an integrating sphere. Their corresponding infrared thermal images are recorded by infrared cameras (Fluke, TiX580).
[0034] The cross-section of the membrane was observed using a transmission electron microscope (TEM, CM100, Philips) at an accelerating voltage of 100 kV. Prior to TEM characterization, all membrane samples were immersed in 10 v / v% glycerol / water for 1 hour and dried in an oven at 40 °C
[26] -
[27] , [43-45]. The surface charge characteristics of the membrane were measured by a streaming potentiostat (SurPASS, Anton Paar). The elemental composition of the membrane surface was analyzed by X-ray photoelectron spectroscopy (XPS, ThermoScientific K-Alpha).
[0035] Next, the membrane separation performance was tested. The separation performance was tested using a laboratory-scale cross-flow RO filtration system. The filtration area was 12 cm 2 The membrane samples were applied to a stainless steel membrane filtration module. After pre-pressing for 3 hours at room temperature (~25°C) with a 2,000 ppm NaCl feed solution at a cross-flow velocity of 22.4 cm / s at 17.0 bar, permeate samples were collected to measure water flux and salt retention. Water flux J v (L m -2 h -1 ) and water permeability A (L m -2 h -1 bar -1 ) is calculated using the following expression:
[0036]
[0037] Where Am (kg) is the mass of the permeate in the time interval Δt (hours), a (m 2 ) is the membrane filtration area, ρ(kg / m 3 ) is the density of water, AP (bar) is the applied pressure, and Δπ (bar) is the transmembrane osmotic pressure.
[0038] The NaCl retention rate (R) and permeability coefficient (B) were calculated using the following expressions
[10] -
[11] :
[0039]
[0040] Among them C f and C p is the NaCl concentration in the feed and permeate based on conductivity measurements (Ultrameter II, Myron L). The water-NaCl permeate-selectivity is expressed by the A / B ratio
[10] -
[11] .
[0041] To evaluate the pollutant removal efficiency of the membrane, filtration tests were performed using feed solutions containing 5 ppm B (pH at ~8.5), or 5 ppm As(III) (pH at ~8.5), or 15 ppm N and 1 ppm P (pH at ~7.5), or 200 ppb of various organic pollutants.
[0042] To evaluate the practical application potential of the membrane, real seawater obtained from Victoria Harbour, Hong Kong, China was used as the feed solution at a test pressure of 55 bar.
[0043] According to the present invention, plasmonic heating is generated at the nanointerface. Figures 1A-5D depict schematic diagrams of film preparation and characterization of the plasmonic response of AgNPs. Figure 1A is a schematic depiction of a conventional interfacial polymerization (IP) process. Figure 1B is a schematic depiction of the IPH-IP process, in which silver nanoparticles (AgNPs) were introduced into the IP reaction interface to serve as nanothermal generators under light irradiation. Figure 2 The XRD patterns of PSf substrate and AgNP-modified PSf substrate are depicted. Figures 3A-3D Modified PSf substrates with different AgNP loadings are depicted ( Figure 3A Labeled as "substrate", Figure 3B Marked as "Sub-Ag50", Figure 3C marked as "Sub-Ag200", and Figure 3D marked as “Sub-Ag400”). Figure 4 is with Figures 3A-3D The corresponding UV-VIS-NIR absorption spectra of each of the four substrates in FIG. Figures 5A-5D is with Figures 3A-3D Infrared thermal images under sunlight corresponding to the four substrates.
[0044] In order to achieve the above-mentioned interfacial plasma heating during the IP reaction, AgNPs were in situ generated on the PSf substrate in advance by reducing AgNO3 with NaBH4. The X-ray diffraction (XRD) pattern of the modified substrate showed characteristic peaks at 38.5°, 44.2°, 64.4°, and 77.4° corresponding to the (111), (200), (220), and (311) diffractions of Ag crystals ( Figure 2 )
[46] -
[47] , thus demonstrating the formation of Ag on its surface. Other obvious peaks (such as those at 17.6°, 22.6°, and 25.8°) may originate from the PSf substrate, as they were observed in both the original and modified substrates. Further characterization of the substrate surface (modified with different AgNO3 solution concentrations) using SEM images and EDS analysis confirmed the formation of AgNPs ( Figures 3A-3D). The increased AgNO3 solution concentration resulted in greater coverage or loading of AgNPs on the substrate surface. The UV-VIS-NIR absorption spectrum of the modified surface showed significantly higher absorption (greater than 90%) at a wavelength of ~400 nm compared to the absorption spectrum of the original substrate (less than 30%) ( Figure 4 ), which can be attributed to the strong plasmon resonance of AgNPs at this wavelength
[48] -
[49] . It is worth noting that the greater coverage or loading of AgNPs on the substrate surface contributes to higher absorption at wavelengths of ~400 nm, resulting in an increase in the surface temperature under solar irradiation ( Figures 5A-5D ).
[0045] The characteristics and separation performance of the polyamide membranes obtained from IPH-IP were also studied. Figures 6A-6D TEM images of membrane cross sections are depicted. Figure 6E-6H SEM images of the membrane surface are depicted. Fig. 7A is a graph of the cavity ratio within the polyamide layer measured using TEM. Figure 7B is a graph of the degree of cross-linking of the polyamide layer. Figure 7C is a graph of the zeta potential of the membrane. Fig.7D is 1kW / m 2 Figure 2 Plot of the separation performance of membranes with different AgNP loadings under different light intensities. Fig. 7E At different light intensities (kW / m 2 ) are graphs showing the separation performance of membranes with different AgNP loadings. Figure 7F is a graph of the separation performance of the present results (red stars) in terms of water permeability and water / NaCl selectivity compared to literature data (black circles).
[0046] The properties of polyamide films with / without AgNPs and with / without illumination are shown. Figures 8A-8D TEM images of membrane cross sections are depicted. Figures 8E-8H SEM images of the membrane surface are depicted. Fig. 9 is a graph of the separation performance of polyamide membranes with and without AgNPs and with and without light irradiation.
[0047] The properties of the polyamide film at different wavelengths of light are further shown. Figures 10A-10D TEM images of membrane cross sections are depicted. Figures 10E-10H SEM images of the membrane surface are depicted. Fig.11 The separation performance of the polyamide membrane at different light wavelengths is depicted.
[0048] The results show that the 2 ) properties of polyamide membranes under . Figures 12A-12D TEM images of membrane cross sections are depicted. Figures 12E-12HDifferent SEM pictures of the membrane surface are depicted.
[0049] Figure 6A-12H The influence of interfacial plasma heating on the characteristics and separation performance of the polyamide membranes according to the invention is demonstrated.
[0050] The increased AgNP loading resulted in more pronounced polyamide nanocavities ( Figures 6A-6D ), larger leaf-like structures ( Figure 6E-6H ), a higher polyamide cavity ratio ( Fig. 7A ) and high cross-linking degree ( Figure 7B The negative charge of the membrane was also enhanced, which may be due to the negatively charged AgNPs. These improved properties simultaneously enhanced the water permeability and NaCl rejection ( Fig.7D ).
[0051] Further experiments with and without AgNPs and with and without light should confirm the improved film properties ( Figures 8A-8H ) and separation performance ( Fig. 9 ) can be attributed to the interfacial plasmon heating induced by AgNPs.
[0052] In addition, experiments at different light wavelengths (e.g., no light, visible light, ~400 nm, and ~600 nm) also confirmed the interfacial plasmon heating effect, as 400 nm light irradiation produced improved membrane properties and separation performance comparable to those of visible light irradiation ( Figures 10A-10H ) and separation performance ( Fig.11 ). However, no light or ∼600 nm light irradiation showed negligible effects, which can be attributed to the fact that the plasmonic response of AgNPs occurs at a wavelength of ∼400 nm.
[0053] Based on the above interfacial plasmon heating induced by AgNPs, further attempts were made to control the interface temperature to tune the membrane characteristics and separation performance under different light intensities: higher light intensity facilitated larger polyamide nanocavities ( Figures 12A-12H ) and better separation performance ( Fig. 7E These outstanding separation properties significantly break the permeability-selectivity trade-off ( Figure 7F ).
[0054] In addition, the interfacial plasma heating effect can also be achieved with other nanomaterials (e.g., Cu). The corresponding polyamide membranes simultaneously show enhanced water permeability and salt rejection ( Fig.13 ), indicating that there is a wide range of photothermal materials to choose from for the plasma heating effect.
[0055] The present invention has application for multifunctional water purification. Figure 14-17The application of the present invention for real seawater desalination and pollutant removal is demonstrated. Regarding real seawater desalination, Fig.14 Corresponding to the membrane's Na + , K + , Cl - and SO4 2- In addition, regarding the desalination of real seawater, Figures 15A-15C Relative temperature intensity in 3D fluorescence spectra corresponding to dissolved organic matter in real seawater and membrane permeate. Figures 16A-16C Graph corresponding to the removal of specific pollutants. Fig.16A is a graph of the rejection of B (5 ppm at a typical seawater pH of ~8.5) and As(III) (5 ppm at a typical groundwater pH of ~8.5). Fig. 16B is a graph of the rejection of N (15 ppm at a typical wastewater pH of -7.5) and P (1 ppm at a typical wastewater pH of -7.5). Fig. 16C is a graph of the rejection of various EDCs (200 ppb at a typical wastewater pH of ~7.5). Fig.17 Figure 2 is a graph showing the retention rate of TFC-Ag200L for 17 common harmful pollutants in different water sources (e.g., boron in seawater, As(III) in groundwater, N, P, EDC, antibiotics, and PFAS in wastewater) and the retention rate of 6 typical ions. The error bars represent the standard deviation using three different samples.
[0056] Regarding real seawater desalination, the TFC-Ag200L membrane showed significant performance in desalination of real seawater (removal of inorganic salts and organic matter) compared to the benchmark commercial membranes ( Fig.14 and Figures 15A-15C )’s huge advantage.
[0057] Regarding pollutant removal, the TFC-Ag200L membrane has a much higher removal efficiency than the benchmark commercial membrane for various pollutants present in different water sources (e.g., B in seawater, As(III) in groundwater, and N, P, and EDC in wastewater). Figures 16A-16C The above results demonstrate the superiority of IPH-IP RO membrane in achieving efficient and extensive removal of various harmful and toxic pollutants commonly found in different water sources ( Fig.17 ), thus revealing great potential for multifunctional water purification applications (e.g., seawater desalination, groundwater treatment, wastewater treatment, and water reuse).
[0058] The above are only specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modification or substitution obvious to those skilled in the art should fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be subject to the scope of protection of the claims.
[0059] References
[0060] The references cited in this application are incorporated herein by reference in their entirety as follows:
[0061] [1] Eliasson, J., The rising pressure of global water shortages. Nature, 2015, 517, (7532), 6.
[0062] [2] Mekonnen, MM; Hoekstra, AY. Four billion people facing severe water scarcity. Sci Adv, 2016, 2, (2), e1500323.
[0063] [3] Culp, TE; Khara, B.; Brickey, KP; Geitner, M.; Zimudzi, TJ; Wilbur, JD; Jons, SD; Roy, A.; Paul, M.; Ganapathysubramanian, B.; Zydney, AL; Kumar, M.; Gomez, ED. Nanoscale control of internal inhomogeneity enhances water transport in desalination membranes. Science, 2021, 371, (6524), 72-75.
[0064] [4] Caldera, U.; Breyer, C., Learning Curve for Seawater Reverse Osmosis Desalination Plants: Capital Cost Trend of the Past, Present, and Future. Water Resources Research, 2017, 53, (12), 10523-10538.
[0065] [5] Shannon, MA; Bohn, PW; Elimelech, M.; Georgiadis, JG; Marinas, BJ; Mayes, AM. Science and technology for water purification in the coming decades. Nature, 2008, 452, (7185), 301-10.
[0066] [6] Grant, SB; Saphores, JD; Feldman, DL; Hamilton, AJ; Fletcher, TD; Cook, PL; Stewardson, M.; Sanders, BF; Levin, LA; Ambrose, RF; Deletic, A.; Brown, R.; Jiang, SC; Rosso, D.; Cooper, WJ; Marusic, I., Taking the "waste" out of "wastewater" for humanwater security and ecosystem sustainability. Science, 2012, 337, (6095), 681-6.
[0067] [7] Qasim, M.; Badrelzaman, M.; Darwish, NN; Darwish, NA; Hilal, N., Reverse osmosis desalination: A state-of-the-art review. Desalination, 2019, 459, 59-104.
[0068] [8] Tang, C.Y.; Yang, Z.; Guo, H.; Wen, J.J.; Nghiem, L.D.; Cornelissen, E., Potable Water Reuse through Advanced Membrane Technology. Environ. Sci. Technol., 2018, 52, (18), 10215-10223.
[0069] [9] Park, HB; Kamcev, J.; Robeson, LM; Elimelech, M.; Freeman, BD. Maximizing the right stuff: The trade-off between membrane permeability and selectivity. Science, 2017, 356, (6343), eaab0530.
[0070]
[10] Werber, JR; Deshmukh, A.; Elimelech, M., The Critical Need for Increased Selectivity, Not Increased Water Permeability, for Desalination Membranes. Environ. Sci. Technol. Lett., 2016, 3, (4), 112-120.
[0071]
[11] Yang, Z.; Guo, H.; Tang, C.Y., The upper bound of thin-film composite (TFC) polyamide membranes for desalination. Journal of Membrane Science (J. Membr. Sci.), 2019, 590, 117297.
[0072]
[12] Bernstein, R.; Belfer, S.; Freger, V., Toward Improved Boron Removal in RO by Membrane Modification: Feasibility and Challenges. Environmental Science and Technology, 2011, 45, (8), 3613-3620.
[0073]
[13] Hyung, H.; Kim, J.-H., A mechanical study on boron rejection by sea water reverse osmosis membranes. Journal of Membrane Science, 2006, 286, (1-2), 269-278.
[0074]
[14] Lim, Y. J.; Goh, K.; Kurihara, M.; Wang, R., Seawater desalination by reverse osmosis: Current development and future challenges in membrane fabrication–A review. Journal of Membrane Science, 2021, 629.
[0075]
[15] Shih, M.-C., An overview of arsenic removal by pressure-driven membrane processes. Desalination, 2005, 172, (1), 85-97.
[0076]
[16] Akin, I.; Arslan, G.; Tor, A.; Cengeloglu, Y.; Ersoz, M., Removal of arsenate[As(V)]andarsenite[As(III)]from water by SWHR and BW-30 reverse osmosis. Desalination, 2011, 281, 88-92.
[0077]
[17] Chen, A. S. C.; Wang, L.; Sorg, T. J.; Lytle, D. A., Removing arsenic and co-occurring contaminants from drinking water by full-scale ion exchange and point-of-use / point-of-entry reverse osmosis systems. Water Res., 2020, 172, 115455.
[0078]
[18] Kimura, K.; Toshima, S.; Amy, G.; Watanabe, Y., Rejection of neutral endocrine disrupting compounds (EDCs) and pharmaceutical active compounds (PhACs) by RO membranes. Journal of Membrane Science, 2004, 245, (1-2), 71-78.
[0079]
[19] Nghiem, LD; Manis, A.; Soldenhoff, K.; AI, Estrogenic hormone removal from wastewater using NF / RO membranes. Journal of Membrane Science, 2004, 242, (1-2), 37-45.
[0080]
[20] Guo, H.; Dai, R.; Xie, M.; Peng, L. E.; Yao, Z.; Yang, Z.; Nghiem, L. D.; Snyder, S. A.; Wang, Z.; Tang, C. Y., Tweak in Puzzle: Tailoring Membrane Chemistry and Structure toward Targeted Removal of Organic Micropollutants for Water Reuse. Environmental Science and Technology Express, 2022, 9, (4), 247-257.
[0081]
[21] Lu, X.; Elimelech, M., Fabrication of desalination membranes by interfacial polymerization: history, current efforts, and future directions. Chem. Soc. Rev., 2021, 50, (11), 6290-6307.
[0082]
[22] Freger, V.; Ramon, G. Z., Polyamide desalination membranes: Formation, structure, and properties. Progress in Polymer Science (Prog. Polym. Sci.), 2021, 122, 101451.
[0083]
[23] Ma, X.-H., Yao, Z.-K., Yang, Z., Guo, H., Xu, Z.-L., Tang, C.Y., Elimelech, M., Nanofoaming of Polyamide Desalination Membranes To Tune Permeability and Selectivity. Environmental Science and Technology Express, 2018, 5, (2), 123-130.
[0084]
[24] Ma, X.; Yang, Z.; Yao, Z.; Guo, H.; Xu, Z.; Tang, C. Y., Tuning roughness features of thin film composite polyamide membranes for simultaneously enhanced permeability, selectivity and anti-fouling performance. Journal of Colloid Interface Sci., 2019, 540, 382-388.
[0085]
[25] Peng, L. E.; Yao, Z.; Liu, X.; Deng, B.; Guo, H.; Tang, C. Y., Tailoring Polyamide Rejection Layer with Aqueous Carbonate Chemistry for Enhanced Membrane Separation: Mechanistic Insights, Chemistry-Structure-Property Relationship, and Environmental Implications. Environmental Science and Technology, 2019, 53, (16), 9764-9770.
[0086]
[26] Peng, L. E.; Jiang, Y.; Wen, L.; Guo, H.; Yang, Z.; Tang, C. Y. Does interfacial vaporization of organic solvent affect the structure and separation properties of polyamideRO membranes? Journal of Membrane Science, 2021, 625, 119173.
[0087]
[27] Gan, Q.; Peng, L. E.; Guo, H.; Yang, Z.; Tang, C. Y. Cosolvent-Assisted Interfacial Polymerization toward Regulating theMorphology and Performance of Polyamide Reverse Osmosis Membranes: Increased m-Phenylenediamine Solubility or Enhanced Interfacial Vaporization? Environmental Science and Technology, 2022, 56, (14), 10308-10316.
[0088]
[28] Di Vincenzo, M.; Tiraferri, A.; Musteata, VE; Chisca, S.; Sougrat, R.; Huang, LB; Nunes, SP; Barboiu, M., Biomimeticartificial water channel membranes for enhanced desalination. Nature Nanotechnol, 2021, 16, (2), 190-196.
[0089]
[29] Lin, L.; Lopez, R.; Ramon, G. Z.; Coronell, O., Investigating the void structure of the polyamide active layers of thin-film composite membranes. Journal of Membrane Science, 2016, 497, 365-376.
[0090]
[30] Wong, M. C. Y.; Lin, L.; Coronell, O.; Hoek, E. M. V.; Ramon, G. Z. Impact of liquid-filled voids within the active layer on transport through thin-film composite membranes. Journal of Membrane Science, 2016, 500, 124-135.
[0091]
[31] Ghosh, AK; Jeong, B.-H.; Huang, X.; Hoek, EMV. Impacts of reaction and curing conditions on polyamide composite reverse osmosis membrane properties. Journal of Membrane Science, 2008, 311, (1-2), 34-45.
[0092]
[32] Wen, Y.; Dai, R.; Li, X.; Zhang, X.; Cao, X.; Wu, Z.; Lin, S.; Tang, C.Y.; Wang, Z., Metal-organic framework enables ultraselective polyamide membrane for desalination and water reuse. Science Advances, 2022, 8, (10), eabm4149.
[0093]
[33] Jauffred, L.; Samadi, A.; Klingberg, H.; Bendix, P. M.; Oddershede, L. B. Plasmonic Heating of Nanostructures. Chem. Rev., 2019, 119, (13), 8087-8130.
[0094]
[34] Elias, RC; Linic, S., Elucidating the Roles of Local and Nonlocal Rate Enhancement Mechanisms in Plasmonic Catalysis. Journal of the American Chemical Society (J.Am.Chem.Soc.), 2022, 144, (43), 19990-19998.
[0095]
[35] Naldoni, A.; Shalaev, VM; Brongersma, ML. Applying plasmonics to a sustainable future. Science, 2017, 356, (6341), 908-909.
[0096]
[36] Schuller, JA; Barnard, ES; Cai, W.; Jun, YC; White, JS; Brongersma, ML. Plasmonics for extreme light concentration and manipulation. Nature Mater, 2010, 9, (3), 193-204.
[0097]
[37] Zhou, L.; Tan, Y.; Ji, D.; Zhu, B.; Zhang, P.; Xu, J.; Gan, Q.; Yu, Z.; Zhu, J., Self-assembly of highly efficient, broadband plasmonic absorbers for solar steam generation. Science Advances, 2016, 2, (4), e1501227.
[0098]
[38] Zhan, C.; Wang, QX; Yi, J.; Chen, L.; Wu, DY; Wang, Y.; Xie, ZX; Moskovits, M.; Tian, ZQ, Plasmonic nanoreactors regulating selective oxidation by energetic electrons and nanoconfined thermal fields. Science Advances, 2021, 7, (10).
[0099]
[39] Hirsch, LR; Stafford, RJ; Bankson, JA; Sershen, SR; Rivera, B.; Price, RE; Hazle, JD; Halas, NJ; West, JL. Nanoshell-mediated near-infrared thermal therapy of tumors under magnetic resonance guidance. Proc Natl Acad Sci USA, 2003, 100, (23), 13549-54.
[0100]
[40] Huschka, R.; Zuloaga, J.; Knight, MW; Brown, LV; Nordlander, P.; Halas, NJ. Light-induced release of DNA from gold nanoparticles: nanoshells and nanorods. Journal of the American Chemical Society, 2011, 133, (31), 12247-55.
[0101]
[41] Ben-Sasson, M.; Lu, X.; Bar-Zeev, E.; Zodrow, K. R.; Nejati, S.; Qi, G.; Giannelis, EP; Elimelech, M., In situ formation of silver nanoparticles on thin-film composite reverse osmosis membranes for biofouling mitigation. Water Research, 2014, 62, 260-70.
[0102]
[42] Yang, Z.; Guo, H.; Yao, ZK; Mei, Y.; Tang, CY. Hydrophilic Silver Nanoparticles Induce Selective Nanochannels in Thin Film Nanocomposite Polyamide Membranes. Environmental Science and Technology, 2019, 53, (9), 5301-5308.
[0103]
[43] Song, X.; Gan, B.; Yang, Z.; Tang, C. Y.; Gao, C. Confined nanobubbles shape the surface roughness structures of thin film composite polyamide desalination membranes. Journal of Membrane Science, 2019, 582, 342-349.
[0104]
[44] Song, X.; Gan, B.; Qi, S.; Guo, H.; Tang, C. Y.; Zhou, Y.; Gao, C., Intrinsic Nanoscale Structure of Thin Film Composite Polyamide Membranes: Connectivity, Defects, and Structure-Property Correlation. Environmental Science and Technology, 2020, 54, (6), 3559-3569.
[0105]
[45] Gan, Q.; Wu, C.; Long, L.; Peng, L. E.; Yang, Z.; Guo, H.; Tang, C. Y. Does Surface Roughness Necessarily Increase the Fouling Propensity of Polyamide Reverse Osmosis Membranes by Humic Acid? Environmental Science and Technology, 2023, 57, (6), 2548-2556.
[0106]
[46] Liu, Y.; Liu, CH; Debnath, T.; Wang, Y.; Pohl, D.; Besteiro, LV; Meira, DM; Huang, S.; Yang, F.; Rellinghaus, B.; Chaker, M.; Perepichka, DF; Ma, D., Silver nanoparticle enhanced metal-organic matrix with interface-engineering for efficient photocatalytic hydrogen evolution. Nature Communications, 2023, 14, (1), 541.
[0107]
[47] Shao, P.; Chang, Z.; Li, M.; Lu, X.; Jiang, W.; Zhang, K.; Luo, X.; Yang, L., Mixed-valence molybdenum oxide as a recyclable sorbent for silver removal and recovery from wastewater. Nature Communications, 2023, 14, (1), 1365.
[0108]
[48] Bastus, NG; Piella, J.; Puntes, V., Quantifying the Sensitivity of Multipolar (Dipolar, Quadrupolar, and Octapolar) Surface Plasmon Resonances in Silver Nanoparticles: The Effect of Size, Composition, and Surface Coating. Langmuir, 2016, 32, (1), 290-300.
[0109]
[49] Christopher, P.; Xin, H.; Linic, S., Visible-light-enhanced catalytic oxidation reactions on plasmonic silver nanostructures. Nat Chem, 2011, 3, (6), 467-72.
[0110] Although the present invention has been described with respect to certain embodiments of the present invention, it will be appreciated that various modifications thereof will become apparent to those skilled in the art upon reading the specification. Therefore, it will be appreciated that the invention disclosed herein is intended to cover such modifications as fall within the scope of the appended claims.
Claims
1. A reverse osmosis (RO) membrane, characterized in that: include: m-phenylenediamine (MPD), trimesoyl chloride (TMC) and n-hexane; Polysulfone (PSf) substrate; and Silver nanoparticles (AgNPs).
2. The RO membrane according to claim 1, characterized in that: A polyamide layer was prepared on the PSf substrate using the MPD, TMC and n-hexane.
3. The RO membrane according to claim 2, characterized in that The polyamide layer on the PSf substrate is prepared by interfacial polymerization (IP) reaction.
4. The RO membrane according to claim 1, characterized in that The AgNPs were generated using inorganic compounds silver nitrate (AgNO3) and sodium borohydride (NaBH4).
5. The RO membrane according to claim 4, characterized in that The AgNPs are generated in situ on the substrate.
6. A method for preparing a reverse osmosis (RO) membrane, characterized in that: The following steps are involved: In situ generation of silver nanoparticles (AgNPs) on PSf substrates; Immersing the PSf substrate in a silver nitrate (AgNO3) solution; pouring a sodium borohydride (NaBH4) solution on the PSf substrate to produce an AgNP-modified substrate; rinsing the substrate with deionized (DI) water; and A polyamide layer was prepared on the AgNP-modified substrate.
7. The method according to claim 6, characterized in that The soaking step also includes shaking for about 10 minutes.
8. The method according to claim 7, characterized in that The shaking was performed at about 50 rpm.
9. The method according to claim 6, characterized in that Any extra AgNO3 solution was removed.
10. The method according to claim 9, characterized in that Any extra AgNO3 solution was removed with a rubber roller.
11. The method according to claim 6, characterized in that The molar mass (mM) concentration of the AgNO 3 solution is in the range of about 50 mM to 400 mM.
12. The method according to claim 6, characterized in that The mM concentration of the NaBH4 solution was about 200 mM.
13. The method according to claim 6, characterized in that The pouring step allows one or more silver ions (Ag + ) is reduced to one or more AgNPs.
14. The method according to claim 6, characterized in that The pouring step also includes shaking for about 10 minutes.
15. The method according to claim 14, characterized in that The shaking was performed at about 50 rpm.
16. The method according to claim 6, characterized in that The washing step was performed for about 5 minutes.
17. The method according to claim 6, characterized in that The step of preparing a polyamide layer on the AgNP-modified substrate is performed by an interfacial polymerization (IP) reaction.
18. The method according to claim 17, characterized in that The IP reaction was initiated by irradiation with simulated sunlight.
19. The method according to claim 18, characterized in that The intensity of the simulated sunlight is about 1 kW / m 2 .
20. The method according to claim 18, characterized in that The simulated sunlight irradiation was performed using a xenon lamp.
21. The method according to claim 18, characterized in that The simulated sunlight was filtered using an air quality factor 1.5 filter.
22. The method according to claim 17, characterized in that The RO membrane is at about 0.5 kW / m 2 Up to 4kW / m 2 prepared under a range of light intensities.
23. The method according to claim 18, characterized in that The RO membranes were prepared using different plasmonic nanomaterials (eg, Cu and Ag).